Prediksi Durasi Kuliah dengan Algoritma Classifier - Rika Harman; Evan Rosiska (InfoTekJar : Jurnal Nasional Informatika dan Teknologi Jaringan, 2020)
Studying and becoming a student for some students is the most exciting thing, they seem to enjoy it very much, it is natural for students in this category to finish their study period on time and some are even faster than the set time. Even though they themselves are also faced with demands about how many credits they have to complete on time, doing assignments, thesis and facing some lecturers' behavior which they think is unusual or they are often called killer terms. But this is different from some certain students, they are impressed, on the contrary they cannot enjoy it, so they become students who are lazy to come to college, lazy to do assignments and also lazy to complete their thesis, this will certainly impact on their study period where it should can be completed on time 4 years instead will be delayed to 5 years, 6 years and even up to 7 and 8 years or some even drop out (DO). Based on data from the Batam Open University (POKJAR) study group, almost 99% of students who study there are working, of which 80% of them can complete their studies on time, as if another 20% are not. This research will discuss what is the root of their problem so that they cannot finish college on time. The results of this study can later be a benchmark for decision making for the Batam Open University study group (POKJAR) towards a better direction so that all parties benefit both students and the management of the study group or the Open University itself.